Gender Representation and Stereotypes in the K-12 English Learner's Materials - Manalo, Ailel Suzzet D. (International Journal of Scientific Research and Management (IJSRM), 2018)
This research is a critical study, which intends to identify the gender representation and stereotypes present in the four K-12 English learner’s materials for Junior High School. Using a content analysis and integrating the findings with the interview responses of selected teachers and students from the Division of City of San Fernando (Ph), the following inferences were generated: male characters showed far more visibility than female characters who also rarely came first in gender pairings; male characters were engaged in more active roles than the female characters who, as well, were often linked with occupations that required less leadership and knowledge-based skills and were low-income generating; female characters were often associated with negative traits, while male characters were often attached with positive traits; domestic roles were almost exclusively attached with female characters; and that there was no indication of gender variance or gender nonconformity in all the learner’s materials analyzed. The researcher recommends that the K-12 English learner’s materials for Junior High School may be revisited. The selection of the literary pieces may consider the works of female authors who penetrated the literary canon. Department of Education may require all textbooks and learner’s materials writers, editors, and publishing companies that work for the department to attend seminars and trainings on gender sensitivity and inclusivity. Overall, these LMs may entail gender sensitivity and genderqueer inclusion.